The impact of built and social environmental characteristics on incidence and estimated risk of dementia. (31st December 2021) - Bagheri, Nasser; Mavoa, Suzanne; Tabatabaei‐Jafari, Hossein; Knibbs, Luke D; Coffee, Neil T; Salvador‐Carulla, Luis; Anstey, Kaarin J
Abstract: Background: Dementia is a public health priority 1 and the current study designed to investigate associations between built and social environmental characteristics and dementia incidence, and the estimated future risk of dementia. Further we investigated spatial variations in dementia risk and dementia incidence to identify unmet areas for policy intervention. Method: We used 25, 511 patients (aged 65 years and older) records in Adelaide between 2011‐2015. In addition to dementia incidence, we calculated a dementia risk score based on risk and protective factors for patients not diagnosed with dementia. The following built and social environment exposures were estimated for each statistical area level 1 (SA1) 2 : social fragmentation, nitrogen dioxide (NO2 ), public open spaces, walkability, socio‐economic status and the length of main roads. We performed multilevel regression analyses to allow for the hierarchical nature of the data and applied spatial cluster analysis to identify areas with high and low risk of dementia. Result: We found that a one standard deviation (SD) increase in NO2 and walkability score was associated with 10% higher odds of any versus no dementia (95% confidence interval (CI): 1%, 21% for NO2 and 0%, 22% for walkability score). For estimated future risk of dementia, a 1‐SD increase in social fragmentation (mobility component) and NO2 was associated with a 1% increase in dementia risk (95% CI: 0, 1%). 1‐SD increases in public open space and socioeconomic status were associated with 3% (95% CI: 0.95, 0.98) and 1% decreases (95% CI: 0.98, 0.99) in dementia risk, respectively. There was spatial heterogeneity in the pattern of dementia incidence and dementia risk. Conclusion: Associations of neighbourhood NO2 level, walkability, public open space and social fragmentation with dementia incidence and estimated future risk of dementia were statistically significant, indicating the potential to reduce the risk through changes in built and social environments. Mapping the estimated future risk of dementia and diagnosed cases of dementia offers a novel approach to identifying areas of unmet need. 1. Towards a dementia plan: a WHO guide. Geneva: WHO; 2018. 2. Australian Statistical Geography Standard (ASGS): Volume 1 ‐ Main Structure and Greater Capital City Statistical Areas, 2016.